2000
DOI: 10.1097/00004872-200018070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stroke by ambulatory blood pressure monitoring versus screening blood pressure measurements in a general population

Abstract: The present study which prospectively investigated the relation between ambulatory blood pressure and first symptomatic stroke risk in a general population demonstrated that (i) ambulatory blood pressure values were linearly related to stroke risk; (ii) ambulatory blood pressures had the stronger predictive power for stroke risk than did screening blood pressure; and (iii) daytime blood pressure better related to stroke risk than did night-time blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
143
2
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 26 publications
5
143
2
5
Order By: Relevance
“…There is a growing body of evidence, [21][22][23][24] including our previous reports, 8,9,25 that ambulatory BP provides better prognostic value than casual BP, although the median follow-up of all these reports was Ͻ10 years. In the present study, we validated the previous findings using data from long-term follow-up (ie, Ͼ10 years).…”
Section: Rhs (95% Cis) For Bp Values As a Continuous Variablementioning
confidence: 98%
See 1 more Smart Citation
“…There is a growing body of evidence, [21][22][23][24] including our previous reports, 8,9,25 that ambulatory BP provides better prognostic value than casual BP, although the median follow-up of all these reports was Ͻ10 years. In the present study, we validated the previous findings using data from long-term follow-up (ie, Ͼ10 years).…”
Section: Rhs (95% Cis) For Bp Values As a Continuous Variablementioning
confidence: 98%
“…Although daytime BP has been reported to be a good predictor of outcomes, 8,[21][22][23][24][25] some studies have shown nighttime BP to be a stronger predictor of cardiovascular mortality. 21,26 The Syst-Eur Trial 21 found that only nighttime BP was a significant predictor of cardiovascular mortality the among placebo and total groups when daytime and nighttime BP were included in the same Cox model.…”
Section: Rhs (95% Cis) For Bp Values As a Continuous Variablementioning
confidence: 99%
“…In hypertensive patients, the absence of a nocturnal BP dipping has been associated with the development of target organ damage, such as left-ventricular hypertrophy 1 and microalbuminuria, 2 and the occurrence of cerebrovascular 3,4 and cardiovascular events. [5][6][7] In some studies, nighttime BP has been found to be a better predictor of cardiovascular risk and mortality than daytime BP, 8,9 but this observation has not been confirmed in all of the studies.…”
mentioning
confidence: 99%
“…4 -6 So far, only 1 large study has examined the prognostic value of ambulatory BP in a general population, the Ohasama study, conducted in a Japanese population, found future cardiovascular deaths to be better predicted by ambulatory BP than office BP. 7,8 In 1993 to 1994, we recorded ambulatory BP in a random sample of 1700 men and women from the general Danish population. Survival status was recorded until October 2003, allowing us to study the relationship between ambulatory BP and mortality in a general Western population for the first time.…”
mentioning
confidence: 99%